2018
DOI: 10.1071/py17088
|View full text |Cite
|
Sign up to set email alerts
|

Models of nutrition-focused continuing education programs for nurses: a systematic review of the evidence

Abstract: Nurses are well-positioned to provide basic nutrition education and reinforce nutrition messages to patients in hospital and primary care settings. Despite this, nurses may not receive adequate training to provide this service, and there is limited opportunity for nurses to engage in nutrition-focused continuing education (CE). The aim of this review was to determine whether nurse nutrition education results in improved knowledge and practices; and explore which models of CE for nutrition may be most acceptabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
6

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
0
17
0
6
Order By: Relevance
“… 19 20 For nurses, continuing professional development (CPD) programmes which are based on active learning models that use case studies, clinical simulations and participatory discussions are more effective than didactic models of learning. 21 The mode of delivery of CPD programmes also needs consideration. Education delivered online offers convenience and flexibility to busy working professionals and students, 22 23 while resulting in equivalent or superior outcomes compared with traditional methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 20 For nurses, continuing professional development (CPD) programmes which are based on active learning models that use case studies, clinical simulations and participatory discussions are more effective than didactic models of learning. 21 The mode of delivery of CPD programmes also needs consideration. Education delivered online offers convenience and flexibility to busy working professionals and students, 22 23 while resulting in equivalent or superior outcomes compared with traditional methods.…”
Section: Introductionmentioning
confidence: 99%
“…Education of healthcare providers in other contexts has been effective in inducing changes to practice, both immediately and over the longer term 19 20. For nurses, continuing professional development (CPD) programmes which are based on active learning models that use case studies, clinical simulations and participatory discussions are more effective than didactic models of learning 21. The mode of delivery of CPD programmes also needs consideration.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review for studies assessing the efficacy of a dual RDN-RN program on health outcomes did not produce any results. However, studies have shown that individualized counselling from dietitians is more beneficial than general nutritional counselling from other health care providers not specifically trained in dietetics [9,10,18]. A narrative review on the role of nurses in nutritional care noted that effective counselling requires training and education, commenting that, ideally, nutrition counselling is conducted by dietitians, but is costly and time-consuming [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the initial nutritional screening of a patient admitted to a hospital is often performed by a Registered Nurse (RN). Nursing is the largest health care occupation in the US, and nurses have a broad scope of practice that uniquely positions them to implement diet interventions through the spectrum of disease development and management [1,9,10]. Interestingly, prior to the development of the dietitian specialist in the 1950s, nurses provided nutrition care as well [11].…”
Section: Introductionmentioning
confidence: 99%
“…Alguns estudos tem acrescentado informações úteis a temática como a síntese realista conduzida por Mogre et al (2016) que elabora um modelo conceitual sobre as características de intervenções que contribuíram para melhoria de competências no cuidado nutricional (incluídos residentes e estudantes de graduação), outros exploraram a oferta de programas de educação continuada em nutrição disponível aos profissionais em áreas específicas como das doenças cardiovasculares ou em ocupações específicas (Johnston, Mathews, Aspry, Aggarwal, & Gianos, 2019;Mitchell, Lucas, Charlton, & McMahon, 2018). Ainda assim, estudos que se ocupam de investigar qualificação dos trabalhadores da saúde no campo da promoção da alimentação saudável permanecem inexplorados.…”
Section: Estudo De Revisãounclassified